Academic word list and CEFR levels: Profiling academic vocabulary in a technical university learner corpus - Khamis, Noorli; Abdul Bareed, Nurhidayah; Ab Rahim, Ina Suryani (Human Resource Management Academic Research Society, 2024)
This study investigates the vocabulary profile in argumentative essays written by students from different disciplines at a technical university in Malaysia. Using Coxhead's (2000) Academic Word List (AWL), the study profiles the students’ academic vocabulary across disciplines. Given the national requirement to align the English course with the Common European Framework of Reference (CEFR), this study also analyses the CEFR levels of vocabulary in the essays to determine whether the students are meeting the expected language proficiency benchmark. The study aims to bridge the gap between learners' current vocabulary use and the vocabulary required to achieve academic writing proficiency, especially in relation to both general academic and discipline-specific language demands. From the vocabulary profiles, this study provides insights that can inform more effective instructional approaches for teaching and learning of academic writing and help instructors tailor their strategies to support students’ progress toward academic proficiency.